2022
DOI: 10.3390/s22030766
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Changes in Magnetic Field and Frequency on the Vibration of a Thin Magnetostrictive Patch as a Tool for Generating Guided Ultrasonic Waves

Abstract: A set of experiments was designed and conducted to investigate the vibrational ultrasonic response of a thin magnetostrictive patch bonded to a glass plate, with changes in static and dynamic magnetic fields applied to the patch. Such arrangements are often used as a means of generating guided waves in pipes or plates, by attaching a patch to a sample’s surface. The effect of varying the applied static and dynamic magnetic field’s amplitudes and directions and the frequency of the dynamic magnetic field was st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Previous work by the authors has established some of the operating conditions that result from these configurations [ 23 , 24 ], including the radiation patterns of the A0, S0 and SH0 guided wave modes. In Configuration 1, no significant Lorentz forces were expected, leaving only magnetostrictive forces as the driving mechanism.…”
Section: Choice Of Magnet and Coil Configurationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work by the authors has established some of the operating conditions that result from these configurations [ 23 , 24 ], including the radiation patterns of the A0, S0 and SH0 guided wave modes. In Configuration 1, no significant Lorentz forces were expected, leaving only magnetostrictive forces as the driving mechanism.…”
Section: Choice Of Magnet and Coil Configurationsmentioning
confidence: 99%
“…These initial tests indicated that variations in B s and B d could lead to the generation and enhancement of specific guided wave modes while suppressing others. Further work conducted by the authors [ 24 ] investigated the effect of variation of further parameters, such as the excitation frequency and the combined variation of B s and B d . It was demonstrated that the magnetostrictive patch provided a wide active transduction range, but that sensitivity was optimum at an excitation frequency of 120 kHz.…”
Section: Choice Of Magnet and Coil Configurationsmentioning
confidence: 99%